Parity transition of radial structure of MHD instability in magnetically confined torus plasmas - Takemura, Yuki; Watanabe, Kiyomasa; Ito, Shu; Satoru, Sakakibara (Scientific reports, 2025)
The study on the parity of the radial profile of radial displacements due to MHD instabilities in magnetically confined torus plasmas is a crucial subject in fusion plasma research. In some experimental devices, only the parity transition from even to odd parity profile (even-to-odd parity transition) has been observed. Now, an odd-to-even parity transition is first observed after the even-to-odd parity transition in the Large Helical Device (LHD). Moreover, the odd-to-even and even-to-odd parity transitions repeatedly occur when the resonant magnetic perturbation (RMP) applied by external coils is large. The even parity profile is driven by the resistive interchange MHD instability, while the odd parity profile is driven by the “Edge” MHD instability. The even-to-odd and odd-to-even parity transitions are inferred to occur when the “Edge” instability becomes unstable and when it stabilizes under the unstable interchange instability, respectively.